In-hospital outcomes and delayed neurologic sequelae of seizure-related endosulfan poisoning. (October 2017) - Moon, J.M.; Chun, B.J.; Lee, S.D.
Highlights: Seizures related to endosulfan poisoning were investigated. Patients showed rapid progression from status epilepticus (SE) to refractory SE (RSE). The Glasgow coma scale might predict progression from SE to RSE. Patients did not develop delayed neurologic sequelae for six months after discharge. Lorazepam should be considered as a first-line antiepileptic drug. Abstract: Purpose: This study investigated the predictive factors for progression from seizure-related endosulfan poisoning to status epilepticus (SE) and refractory SE (RSE). This study also investigated delayed neurologic sequelae in seizure-related endosulfan poisoning. Methods: This retrospective, observational case series consisted of 73 patients who developed at least one seizure after endosulfan ingestion. Results: The progression rates from seizure-related endosulfan poisoning to SE and from SE-related endosulfan poisoning to RSE were 78.1% and 54.4%, respectively. The SE and RSE fatality rates were 19.2% and 41.9%, respectively. No patients reported the development of delayed neurological sequelae at least six months after discharge. Glasgow coma scale (GCS) score were identified as an independent factor for progression from seizure-related endosulfan poisoning to SE and from SE-related endosulfan poisoning to RSE. Lorazepam administration was independently associated with preventing progression from SE-related endosulfan poisoning to RSE. Conclusion: Seizure-related endosulfan poisoning had higher progression rates to SE and RSE and higher fatality rates than other drug-induced seizures. However, delayed neurologic sequelae after discharge were not demonstrated. Due to the high progression rates from seizure-related endosulfan poisoning to SE and RSE and the absence of an established treatment for SE-related endosulfan poisoning, physicians should aggressively treat patients who experience a seizure after endosulfan poisoning and who present with decreased GCS score. Lorazepam should be considered a first-line anti-epileptic drug for controlling seizures in patients with endosulfan poisoning.